International Class Program UIN Malang as an Effort in Actualizing International Reputable University - Nikmah, Faridatun; Syari'ah, Atiris; Nabilah, Nafa (QUALITY, 2023)
In response to globalization's challenges, educational institutions in Indonesia have begun to develop education oriented towards reforming quality, management, and curriculum with international standards. One of them is through the formation of an international class that is expected to be able to compete at the global level. To realize this, UIN Malang carries the vision of "The realization of an integrative higher education in combining science and Islam with an international reputation." Based on this vision, this study seeks to find out how to implement and form UIN Malang's support for the International Class Program at the Tarbiyah and Teacher Training Faculty to internationalize the campus. This study uses a qualitative approach that emphasizes the interpretation of the data obtained. The problem in the field is the lack of cooperation between layers at the university. It has an impact on the speed of the internationalization process of the UIN Malang.Program Kelas Internasional UIN Malang sebagai Upaya Mewujudkan Universitas Bereputasi Internasional. Menanggapi tantangan globalisasi, lembaga pendidikan di Indonesia mulai mengembangkan pendidikan yang berorientasi pada reformasi mutu, manajemen, dan kurikulum yang berstandar internasional. Salah satunya melalui pembentukan kelas internasional yang diharapkan mampu bersaing di tingkat global. Untuk mewujudkan hal tersebut, UIN Malang mengusung visi “Terwujudnya pendidikan tinggi yang integratif dalam memadukan ilmu pengetahuan dan Islam yang bereputasi internasional.” Berdasarkan visi tersebut, penelitian ini berupaya untuk mengetahui bagaimana implementasi dan bentuk dukungan UIN Malang terhada Program Kelas Internasional Fakultas Ilmu Tarbiyah dan Keguruan untuk menginternasionalkan kampus. Penelitian ini menggunakan pendekatan kualitatif yang menekankan pada interpretasi data yang diperoleh. Hasil dari penelitian ini adalah diketahui adanya permasalahan di lapangan yakni kurangnya kerjasama antar lapisan di universitas. Hal tersebut berdampak pada percepatan proses internasionalisasi UIN Malang.